Metabolic fingerprinting of Sabah Ruellia tuberosa plant extracts for the identification of potential anticancer compounds - Jan Renee Stephanie Jiorry (2014)
Ruellia tuberosa, commonly known as Minnie Root or Cracker Plant, is a traditional medicinal plant used for its diuretic, antidiabetic, and antipyretic properties. Recent findings suggest significant anticancer activity, particularly against breast cancer (MCF-7) cells. This study aimed to identify the potential anticancer compounds in Sabah's R. tuberosa through a metabolic fingerprinting approach using gas chromatography-mass spectrometry (GC-MS). A total of 15 compounds were identified in the leaf extract, 10 in the stem, and 10 in the root. Compounds such as squalene, stigmasterol, campesterol, vitamin E, and lupeol were consistently found and highly speculated to contribute to anticancer activity. Chemical databases were built using PCDL software, and the compounds were correlated with MTT assay data. The findings encourage further isolation and functional analysis of these bioactives to validate their cytotoxic effects on MCF-7 cells.